Pembelajaran Memproduksi Teks Eksplanasi Dengan Menggunakan Metode Nature Learning Pada Peserta Didik - Nina Marliani; Titin Nurhayatini; Meity Suratiningsih (FKIP, Universitas Palangka Raya, 2024)
This research was conducted because of the low ability of students in writing, one of which is in producing explanatory texts by palying attention to the structure and linguistic rules. Factors that can cause this are the lack of students in imagining and the inffectiveness of the learning methods used by educators. One of the learning methods that can increase students imagination in writing explanatory texts is the nature learning method. This study used a quasi-experimental method with a pretest and final test design and a control group. The results showed that the ability of students increased in learning to produce explanatory texts by paying attention to the structure and linguistic rules. There was an increase in the average pretest score from 46,35 to 87,92 in the experimental class posttest. There is a significant difference between the learning outcomes the learning outcomes of students in the experimental and control class, with the average value of the experimental class posttest of 87,92 while in the control class it is 58,92.